2019
DOI: 10.1002/bit.27145
|View full text |Cite
|
Sign up to set email alerts
|

Combined dissolved oxygen tension and online viscosity measurements in shake flask cultivations via infrared fluorescent oxygen‐sensitive nanoparticles

Abstract: Oxygen supply is one of the most critical process parameters in aerobic cultivations.To assure sufficient oxygen supply, shake flasks are usually used in combination with orbital shaking machines. In this study, a measurement technique for the dissolved oxygen tension (DOT) in shake flask cultures with viscosity changes is presented. The movement of the shaker table is monitored by means of a Hall effect sensor. For DOT measurements, infrared fluorescent oxygen-sensitive nanoparticles are added to the culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…A more quantitative confirmation by directly measuring the DOT levels during the cultivation was not done as the focus of this study is on the improvement of the gas-liquid mass transfer by the newly proposed flask design. A deeper quantitative characterization with respect to the DOT levels would need a carefully designed experimental set-up, e.g., by using oxygen-sensitive nanoparticles ( Ladner et al, 2019 ) as conventional approaches to measure DOT in shake flasks can lead to erroneous results ( Hansen et al, 2011 ). However, it could clearly be demonstrated that with the newly proposed perforated ring flasks design non-oxygen limited conditions at the OTR levels usually only seen in stirred tank bioreactors can be achieved in shaken bioreactors.…”
Section: Resultsmentioning
confidence: 99%
“…A more quantitative confirmation by directly measuring the DOT levels during the cultivation was not done as the focus of this study is on the improvement of the gas-liquid mass transfer by the newly proposed flask design. A deeper quantitative characterization with respect to the DOT levels would need a carefully designed experimental set-up, e.g., by using oxygen-sensitive nanoparticles ( Ladner et al, 2019 ) as conventional approaches to measure DOT in shake flasks can lead to erroneous results ( Hansen et al, 2011 ). However, it could clearly be demonstrated that with the newly proposed perforated ring flasks design non-oxygen limited conditions at the OTR levels usually only seen in stirred tank bioreactors can be achieved in shaken bioreactors.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers use shake flasks for the optimization of growth conditions. These shake flasks do not require any special instruments (Ladner et al 2019 ). However, unlike bioreactors, standard cultivation of E. coli in shake flasks is done in batches.…”
Section: Essential Components Of E Coli -Based Exp...mentioning
confidence: 99%
“…Shake Flasks Shake flask fermentations are normally carried out in a laboratory and are widely used to investigate microbial culture behavior on a small scale, mainly to explore feasibility [55]. In bioprocess development applications, the flasks are mainly used for screening and early bioprocess development, which, in medium-level optimization and the preparation of starter cultures in shake flasks, are applied as a pre-culture of stirred-tank fermentation [56]. In addition, the shake flask system enables the performance of a high number of cost-efficient parallel fermentation procedures on a small scale within a set of optimum fermentation conditions [55,57].…”
Section: Current Status and Challengesmentioning
confidence: 99%